2012
DOI: 10.1371/journal.pone.0047740
|View full text |Cite
|
Sign up to set email alerts
|

CD200R1 Supports HSV-1 Viral Replication and Licenses Pro-Inflammatory Signaling Functions of TLR2

Abstract: The CD200R1:CD200 axis is traditionally considered to limit tissue inflammation by down-regulating pro-inflammatory signaling in myeloid cells bearing the receptor. We generated CD200R1−/− mice and employed them to explore both the role of CD200R1 in regulating macrophage signaling via TLR2 as well as the host response to an in vivo, TLR2-dependent model, herpes simplex virus 1 (HSV-1) infection. CD200R1−/− peritoneal macrophages demonstrated a 70–75% decrease in the generation of IL-6 and CCL5 (Rantes) in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 52 publications
0
32
0
1
Order By: Relevance
“…Changes in CD200/CD200R expression levels have been reported to occur after in vivo infection with a variety of microbial pathogens (19,21,23,25,27,52), and this also appears to be the case during RRV infection of RM. Specifically, de novo infection of eSPF RM with either WT BAC or vCD200 NS resulted in observable fluctuations in CD200R expression levels in both myeloid cells and lymphocytes in the weeks following infection, with the most notable changes in CD200R levels occurring in DCs, monocytes, and B cells.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Changes in CD200/CD200R expression levels have been reported to occur after in vivo infection with a variety of microbial pathogens (19,21,23,25,27,52), and this also appears to be the case during RRV infection of RM. Specifically, de novo infection of eSPF RM with either WT BAC or vCD200 NS resulted in observable fluctuations in CD200R expression levels in both myeloid cells and lymphocytes in the weeks following infection, with the most notable changes in CD200R levels occurring in DCs, monocytes, and B cells.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, it is possible that development of an inflammatory environment could promote RRV replication in vivo, and as such, inhibition of immune responses by vCD200 early after infection may have the added effect of diminishing the overall levels of viral replication that can be achieved. On the other hand, recent findings with HSV-1 suggest that CD200/CD200R signaling may be capable of directly promoting viral replication in vivo, independently of its effects on immune responses and through as-yet-identified mechanisms (27). If CD200/CD200R signaling were also involved in promoting RRV replication in vivo, it could be envisioned that vCD200 NS-infected animals might display higher levels of replication than WT BAC-infected animals if the RRV vCD200 protein were somehow involved in disrupting or altering normal CD200/ CD200R interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CD200R-CD200 axis has also been reported as a co-stimulatory axis (Borriello et al, 1997;Wang et al, 2019). Furthermore, CD200R is required to 'license' TLR2mediated immune activation by Herpes Simplex Virus 1 in macrophages (Soberman et al, 2012), and the CD200R/CD200 axis in some cases was suggested to regulate protective antitumor responses (Erin et al, 2015;Erin et al, 2018;Liu et al, 2016). Taken together, although CD200R is generally considered to be an inhibitory receptor, there are data that suggest a more versatile and/or complex functionality of CD200R.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, TLR2 signaling appears to be important in controlling HSV replication in the brain [130]. Interestingly, however, TLR2 has also been described as contributing to lethality of mice with HSV infection in the central nervous system by dramatically increasing the inflammatory response [131], in a manner regulated by the surface glycoprotein CD200R1 [132]. This concept that CNS inflammation can promote pathogenesis in HSV encephalitis is supported by other murine studies [6567, 133].…”
Section: Immune Control Of Hsv Infectionmentioning
confidence: 99%